The impact of flexible working hours towards employee's productivity at Telekom Research and Development Sdn. Bhd. (TMRND) in Cyberjaya / Nurfarahana Syahera Omar - Omar, Nurfarahana Syahera (Faculty of Business and Management, 2018)
This study examined the impact of flexible working hours toward employee's productivity at Telekom Research and Development Sdn. Bhd. (TMR D) in Cyberjaya. The respondents of this research are the employees in Telekom Research and Development Sdn. Bhd. (TMRND) in Cyberjaya. The researcher used correlation research design in this study. The data analyzed by using SPSS version 21. The data of this study were gathered through the distribution of questionnaires and sampling technique used for this study was cluster sampling technique in order to select from the population of the respondents in this organization. The result identified that there was a significant impact of flexible working hours towards employee's productivity. Moreover, the result also shows that there was a positive significant relationship between flexible working hours and employee's productivity. In this study, 2 hypotheses were tested and through the findings, it was found that the statement of "My motivation level at work can be increased through FWHs" has the highest correlation toward employee's productivity. Furthermore, the relationship between flexible working hours and employee's productivity proved that there is a significant relation hip. This study is aim to help management of Telekom Research and Development Sdn. Bhd. (TMRND), Cyberjaya to focusing on employees' productivity by applying the flexible working hours with more efficient in order to increase employee's productivity thus leading to greater organization in the future.